Parental depression and the challenge of preventing mental illness in children. - Ramchandani, P; Murphy, SE (2013)
Parental depression is a risk factor for psychiatric problems in children and adolescents. Exciting scientific developments have elucidated potential early mechanisms of intergenerational risk transmission and new models of intervention may help to prevent some childhood problems. However, caution is needed in interpreting such associations as causal and in targeting interventions appropriately.